Pengaruh Rendaman Eceng Gondok (Eichhornia crassipes [Mart.] Solms) Terhadap Daya Predasi Mesocyclop jakartensis Alekseev - Dheanda Absarina; Rully Rahadian; mochamad Hadi (Jurnal Akademika Biologi, 2015)
Aedes aegypti has been reported as vectors of diseases, including dengue fever (dengue hemorrhagic fever) and Chikungunya. Various efforts have been done to overcome A. aegypti either physically, chemically and biologically control. However, these efforts have not been successful in reducing the density of the vector. The objectives of this study was to compare predation of M. jakartensis on A. aegypti mosquito larvae in several type of water i.e., well water (control), hyacinth infusion and hay infusion. The research method used complete randomized factorial design. Its effect on predation capability test of M. jakartensis used bioassay method on 25 initial instar larvae and 5 individuals of M. jakartensis. Predation capabilities test was analyzed using one-way ANOVA test. Correlation of the chemical factors on capabilities of M. jakartensis predation on the treatments was analyzed statistically using the Spearman test. The results show that predation capabilities of                      M. jakartensis on A. aegypti larvae are as follows, control > Hyacinth (3: 7) > Hay (1: 9) > Hyacinth (1:9). The percentage of predation for each treatment are 93,3; 72,0; 66,7 and 64,0%, respectively. Statistically, predation capabilities of M. jakartensis on A. aegypti larvae in each treatmens is not significantly different (P > 0.05). Hyacinth infusion is unproven in improving the predation of M. jakartensis on A. aegypti larvae, but it does not inhibit capabilities of M. jakartensis predation.  Keywords : Aedes aegypti, Eichhornia crassipes, Mesocyclop jakartensis